2022
DOI: 10.1177/13524585221108080
|View full text |Cite
|
Sign up to set email alerts
|

No increase of serum neurofilament light in relapsing-remitting multiple sclerosis patients switching from standard to extended-interval dosing of natalizumab

Abstract: Background: Accumulating evidence supports the efficacy of administering natalizumab (NZ) with extended-interval dosing (EID) in patients with relapsing-remitting multiple sclerosis (RRMS). Objectives: We switched NZ dosing from 4-week to 6-week intervals in patients with RRMS, and investigated the effect on serum neurofilament light chain (sNfL) concentrations. Methods: We included two cohorts of patients with RRMS treated with NZ: one received the standard-interval dosing (4 weeks) at baseline, and were swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…active RRMS/CIS patients was 9.1 ng/L (IQR; 4.2-25.8), that is 2.5 times higher than in patients with stable disease, 16 and the individual sNfL CV was 33%, which was twice that of stable RRMS controls.…”
Section: Discussionmentioning
confidence: 78%
“…active RRMS/CIS patients was 9.1 ng/L (IQR; 4.2-25.8), that is 2.5 times higher than in patients with stable disease, 16 and the individual sNfL CV was 33%, which was twice that of stable RRMS controls.…”
Section: Discussionmentioning
confidence: 78%
“…While other DMTs have shown convincing decreases of plasma/ serum NfL, the effect has been modest with teriflunomide [25,30]. Although, our study population was limited to only 12 patients, who were of older age where the variability of plasma NfL is higher [31], our results warrant further investigations to explore if teriflunomide affects the penetrans of NfL from CSF to blood.…”
Section: Discussionmentioning
confidence: 80%
“…These results add to the growing body of evidence from real-world clinical practice that the effectiveness of natalizumab on clinical end points (relapses and disease progression) and MRI end points is maintained for patients who switch from Q4W dosing to EID 79 and are consistent with those of a recently published prospective study that found sNfL levels were unchanged during 12 months of follow-up in patients who switched from natalizumab Q4W to every - 6 -week (Q6W) dosing. 36…”
Section: Discussionmentioning
confidence: 99%